PERSPEKTIF SEMIOTIKA PROBLEMATIKA TANDA PADA PERSENGKETA MEREK DAGANG TERDAFTAR STUDI KASUS: “MEREK DAGANG PS. GLOW DENGAN MEREK MS. GLOW”: SEMIOTIC PERSPECTIVE OF MARKS PROBLEMATICS IN REGISTERED TRADEMARK DISPUTESCASE STUDY: PS. GLOW TRADEMARK WITHMS. GLOW BRAND - Fadly Latif; Drajatno Widi Utomo; Acep Iwan Saidi (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
Trademark protection in Indonesia provides an opportunity for brand owners who feel that their brand is used by other parties to legally dispute, by filing a lawsuit against the registered mark to the Commercial Court in the form of compensation or termination of all actions on the use of the mark, this effort is called a civil legal action. The registered trademark dispute between PS Glow and MS Glow at the Surabaya commercial court which became a research case study, reports on the assumption of similarity became research from a semiotic perspective because brands are signs, so the marks on brand objects are analyzed in order to be able to provide conclusions on the similarities reported in real terms. scientific. This study uses a descriptive-qualitative approach using the semiotic method by Charles Sander Pierce, the procedure used is the visual objects that exist in the two disputing brands, namely images, colors and fonts and describe the messages and meanings contained therein. The results of the research provide scientific data from a semiotic perspective on legal issues regarding disputes over registered trademarks, thus the researcher hopes that this can be a reference in providing information on answers to the assumption of similarities in trademarks in dispute. The Semiotics method used in this research can become a recommendation for relevant stakeholders in making decisions in dealing with trademark legal issues in Indonesia. As well as being a recommendation for further research in answering sign problems specifically on trademarks that are more in-depth.